ショウワ キチ HUSAFELL ニオケル ELF-VLF ホウシャ ノ キョウヤクセイ c. ジキケンナイ ノ ハドウ リュウシ ソウゴ サヨウ ダイ2カイ キョクイキ ニオケル デンリケン ジキケン ソウゴウ カンソク シンポジウム PART 1 - 佐藤, 夏雄; サトウ, ナツオ; 鮎川, 勝; アユカワ, マサル; 福西, 浩; フクニシ, ヒロシ; SATO, Natsuo; AYUKAWA, Masaru; FUKUNISHI, Hiroshi (1980)
P(論文) 昭和基地のほぼ地磁気共役点にあたる,アイスランドのHusafelにおいて,1977年7月29日から約50日間,ELF-VLF放射の共役点観測を行った.共役性についていえば,(1)昼間出現するポーラコーラス,準周期的(QP)放射の共役性は良い,(2)バーストタイプのティスクリート放射,オーロラコーラスの共役性は悪く,おもに北半球側が強い,(3)オーロラヒスの共役性は悪く,南半球(冬半球)側が圧倒的に強い.これらの観測結果から共役性の良いポーラコーラス,QP放射は磁気圏内の赤道面付近で発生し,磁力線に沿って伝搬しているものと理解できる.またオーロラヒス,バーストタイプ放射の非共役性は,電離層内の電子密度,磁場強度,磁力線の伏角等の南北半球での非対称およびこれらの放射の発生領域に依存すると思われる. Conjugate observations of ELF-VLF emissions, magnetic pulsations and auroras were carried out at Syowa Station in Antarctica and Husafell in Iceland from July 29, 1977 to September 18,1977. Husafell is located at a distance of about 50 km from the conjugate point of Syowa Station. Conjugacies of ELF-VLF emissions depend on emission types, such as polar chorus, quasiperiodic emissions, burst of discrete emissions and auroral hiss. Polar chorus and quasi-periodic emissions are observed simultaneously at the conjugate-pair stations. This suggests that the emissions are generated near the equatorial region in the outer magnetosphere and propagate to the both hemispheres along the field lines of force. Conjugacy of bursts of discrete emissions and auroral hiss is generally low. The emission intensity of auroral hiss is much stronger at Syowa Station (winter hemisphere) than at Husafell (summer hemisphere). Just the opposite tendency is observed for bursts of discrete emissions. The low conjugacy of these emissions may depend on the differences in geophysical conditions, such as the magnetic field, magnetic dip angle and the plasma density and also it depends on properties of the generation region of the emissions. departmental bulletin paper